Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Kementerian Agama Kabupaten Karawang - Mutma Innatus Salwa; Suroso Suroso; Maman Mulya Karnama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The primary goal of this research is to get knowing of how work discipline and its environment affect productivity within the Ministry of Religion, Karawang Regency workplace. Quantitative verification research is the core of this research. A total of sixty-three participants were surveyed from the Karawang Regency Ministry of Religion. This was a Total sampling strategy, and 63 people completed the survey. The online survey served as a data collection tool, while SPSS 16 multiple linear regression analysis provided the results. Employee performance (y) is influenced by two factors Partially, according to research. Namely environment of work (x1) and discipline of work (x2). If the calculated of F value is bigger than critical of value (33.136 > 3.15), then these two factors have a combined influence of 51.9%.